Costs for Breast Cancer Care in the Military Health System: An Analysis by Benefit Type and Care Source. Issue 11 (11th April 2018) - Eaglehouse, Yvonne L; Manjelievskaia, Janna; Shao, Stephanie; Brown, Derek; Hofmann, Keith; Richard, Patrick; Shriver, Craig D; Zhu, Kangmin
Abstract: Introduction: Breast cancer care imposes a significant financial burden to U.S. healthcare systems. Health services factors, such as insurance benefit type and care source, may impact costs to the health system. Beneficiaries in the U.S. Military Health System (MHS) have universal healthcare coverage and access to a network of military facilities (direct care) and private practices (purchased care). This study aims to quantify and compare breast cancer care costs to the MHS by insurance benefit type and care source. Materials and Methods: We conducted a retrospective analysis of data linked between the MHS data repository administrative claims and central cancer registry databases. The institutional review boards of the Walter Reed National Military Medical Center, the Defense Health Agency, and the National Institutes of Health Office of Human Subjects Research reviewed and approved the data linkage. We used the linked data to identify records for women aged 40–64 yr who were diagnosed with breast cancer between 2003 and 2007 and to extract information on insurance benefit type, care source, and cost to the MHS for breast cancer treatment. We estimated per capita costs for breast cancer care by benefit type and care source in 2008 USD using generalized linear models, adjusted for demographic, pathologic, and treatment characteristics. Results: The average per capita ( n = 2, 666) total cost for breast cancer care was 66, 300 [standard error (SE) 9, 200] over 3.31 (1.48) years of follow-up. Total costs were similar between benefit types, but varied by care source. The average per capita cost was 34, 500 (3, 000) for direct care ( n = 924), 96, 800 (4, 800) for purchased care ( n = 622), and 60, 700 (3, 900) for both care sources ( n = 1, 120), respectively. Care source differences remained by tumor stage and for chemotherapy, radiation, and hormone therapy treatment types. Conclusions: Per capita costs to the MHS for breast cancer care were similar by benefit type and lower for direct care compared with purchased care. Further research is needed in breast and other tumor sites to determine patterns and determinants of cancer care costs between benefit types and care sources within the MHS.